(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
Advertising persuasion is a complex communicative process grounded in the interaction of attention, memory, emotion, linguistic prediction, semantic activation, conceptual framing, and multimodal integration. Contemporary advertisements do not merely transmit information about products and services; they organise perception, activate culturally shared knowledge, guide evaluation, and construct desirable relationships between brands and consumers. The present study investigates the cognitive and neurolinguistic foundations of advertising persuasion through an integrated analysis of attentional salience, working-memory demands, emotional valence, semantic priming, conceptual metaphor, presupposition, syntactic compression, personalisation, and verbal-visual congruence. The empirical material comprises a pilot corpus of fifty English-language advertising messages representing technology, cosmetics and personal care, automotive products, financial services, food and non-alcoholic beverages, and digital platforms. Advertising materials associated with Nike and Coca-Cola were excluded to avoid dependence on extensively analysed canonical campaigns. The study combines cognitive-discursive analysis, pragmatic analysis, conceptual metaphor analysis, and a theoretically informed interpretation of findings from psycholinguistic, electrophysiological, and consumer-neuroscience research. The results indicate that the persuasive potential of advertising is strengthened when messages achieve attentional prominence without excessive cognitive load, connect new commercial information with previously activated semantic associations, employ emotionally relevant but comprehensible framing, and integrate verbal and visual information coherently. Positive framing, personalisation, semantic priming, conceptual metaphor, evaluative intensification, and linguistic compression were among the most recurrent mechanisms in the corpus. The findings further demonstrate that neurolinguistic evidence should not be interpreted as direct proof of purchasing behaviour. Neural and electrophysiological measures provide information about particular stages of attention, semantic integration, affective processing, and motivational relevance, but they require contextual interpretation and behavioural validation. The study concludes that effective advertising persuasion emerges from the coordinated organisation of cognitive accessibility, emotional significance, linguistic form, and contextual relevance rather than from any single persuasive technique